Examining the impact of parasocial interaction and social presence on impulsive purchase in live streaming commerce context - Huang, Yi; Mohamad, Siti Hajar (Frontiers in Communication, 2025)
In recent years, along with the rapid development of Internet technology and drastic changes in consumption patterns, live streaming commerce has gradually become an emerging business model that attracts the participation of consumers. Based on parasocial interaction and social presence created by live streaming commerce, this study uses SmartPLS software to exam the impact of parasocial interaction and social presence on impulsive purchase in live streaming commerce context. According to an empirical analysis of 407 valid questionnaire data from China through an online survey, consumers’ social anxiety and fear of missing out have a significant positive effect on parasocial interaction, while their narrative involvement has a non-significant effect on parasocial interaction. Social presence has a significantly positive effect on impulsive purchase. Consumers’ narrative involvement and smartphone addiction had a significant positive effect on their social presence. This study extends existing research findings regarding consumer impulsive purchase on live streaming commerce. In addition, this study provides evidence that consumers’ parasocial interaction and social presence mediate the relationship between consumer characteristics and impulsive purchase.